EVALUATION OF BUDGET EFFICIENCY POLICY ON TRAINING PROGRAMS AT THE CLASS A MANPOWER TRAINING CENTER UPTD OF NORTH SULAWESI PROVINCE - Sumakul, Richie; Pangemanan, Fanley N; Egeten, Maxi (Journal of Public Administration and Government, 2026)
The budget efficiency policy under Presidential Instruction No. 1 of 2025 threatens the sustainability of vocational training programs at regional training centers (BLK UPTD), particularly at the Class A UPTD Vocational Training Center of North Sulawesi Province (BLK Bitung), the only active government-run training institution in the region. This study aims to evaluate the implementation and impact of the budget efficiency policy on training program quality and to formulate strategies for sustaining the institution. A qualitative case study approach was employed through in-depth interviews, observation, and documentation review, analyzed using an integrated model combining Dunn's (2018) criteria, Stufflebeam's (1971) CIPP framework, Van Meter & Van Horn's (1975) implementation model, and Becker's (1993) human capital perspective. Results reveal that a 6.75% budget cut with only 65% actual realization led to 61.7% dependency on national budget funds and 48.5% of participants lacking access to competency certification, with four of six Dunn criteria rated low. The absence of functional civil servant instructors does not stem from budget cuts per se, but reflects the actual structural reality of unfilled functional positions within the BLK. The study concludes that BLK Bitung is in a state of pseudo-resilience—appearing statistically functional yet structurally fragile—necessitating immediate civil servant instructor recruitment, APBD revitalization, and reformulation of funding mechanisms.